Maine Museums - Staff, Editorial (Maine Policy Review, 2015)
This map and listing of Maine museums by location shows some of the many museums in the state, classified as history, art, mixed (e.g., art + history), and other. The list of museums and historical societies is adapted from one provided by Maine Archives & Museums and is not an exhaustive list of all museums. The map was produced with support from the Spatial Informatics group in the School of Computing and Information Science, University of Maine.